A thermodynamic framework for modelling membrane transporters. (21st November 2019) - Pan, Michael; Gawthrop, Peter J.; Tran, Kenneth; Cursons, Joseph; Crampin, Edmund J.
Highlights: The behaviour of membrane transporters is constrained by the laws of thermodynamics. We propose an energy-based framework (bond graphs) for modelling transporters. This framework captures fundamental thermodynamic constraints in transporters. We apply the methodology to two specific transporters: SERCA and Na + /K + ATPase. Abstract: Membrane transporters contribute to the regulation of the internal environment of cells by translocating substrates across cell membranes. Like all physical systems, the behaviour of membrane transporters is constrained by the laws of thermodynamics. However, many mathematical models of transporters, especially those incorporated into whole-cell models, are not thermodynamically consistent, leading to unrealistic behaviour. In this paper we use a physics-based modelling framework, in which the transfer of energy is explicitly accounted for, to develop thermodynamically consistent models of transporters. We then apply this methodology to model two specific transporters: the cardiac sarcoplasmic/endoplasmic Ca 2+ ATPase (SERCA) and the cardiac Na + /K + ATPase.